Microstructure tailoring of Al-containing compositionally complex alloys by controlling the sequence of precipitation and ordering - Laube, Stephan; Schellert, Steven; Srinivasan Tirunilai, Aditya; Schliephake, Daniel; Gorr, Bronislava; Christ, Hans-Jürgen; Kauffmann, Alexander; Heilmaier, Martin (Acta materialia, 2021)
•Refractory metal-based compositionally complex alloys exhibit a two-phase microstructure.•The room temperature crystal structure can be tailored by the phase transition sequence.•Differential scanning calorimetry reveals both, order reaction and phase separation.•The Al concentration has a significant influence on the order reaction. Refractory metal-based, Al-containing compositionally complex alloys (RCCA) are promising candidates for high-temperature structural applications. To shed light on the complex phase transitions, thermodynamic calculations were performed to select two representative alloys with different sequences in phase transitions. Samples of these compositions were synthesized by arc melting of pure elements followed by a homogenization treatment to experimentally verify the room temperature microstructure and assess the phase transitions. Differential scanning calorimetry (DSC), scanning (SEM) and transmission electron microscopy (TEM) studies after the homogenization and quenching revealed multiple distinct sequences of transitions: (i) 82(TaMoTi)-8Cr-10Al (in at.%) exhibits a solid-state phase separation concurrent with ordering of the precipitates. This results in a disordered matrix with ordered precipitates. Thermal analysis indicates that while cooling from the high-temperature A2 phase, the phase separation and ordering are spread out over a large temperature range (approx. 750 – 1250°C), with a peak at 1055°C. (ii) In the 77(TaMoTi)-8Cr-15Al alloy, a continuous phase transition at 1155°C leads to a single-phase B2 matrix with planar faults. At slightly lower temperatures (approx. 1096°C), phase separation occurs resulting in a B2 matrix with segregation at planar faults and A2 precipitates. In both investigated compositions, the A2 phase is enriched in Ta and Mo. Conversely, the B2 phase is enriched in Al and Ti, while Cr is uniformly distributed in the phases. [Display omitted]